Cash for your trash : scrap recycling in America - Zimring, Carl A., 1969- (Rutgers University Press, 2005)
In Cash for Your Trash, Carl A. Zimring provides a fascinating history of scrap recycling, from colonial times to the present. Integrating findings from archival, industrial, and demographic records, and moving beyond the environmental developments that have shaped modern recycling enterprises, Zimring offers a unique cultural and economic portrait of the private businesses that made large-scale recycling possible.